A cholestatic type of hepatitis A in a child - Sjamsul Arief; Retno Hernik; Agung Nugrohowidhi; Boerhan Hidayat (Indonesian Pediatric Society, 2001)
This paper reports a case of cholestatic type hepatitis A, a rare clinical manifestation of hepatitis A in children. The diagnosis was based on the presence of IgM Anti HAV, symptoms longer than 8 weeks, bilirubin concentration exceeding 10g/dl, and absence of substantial hepatocellular and biliary damage. Corticosteroid therapy resulted in complete recovery.